Emerging functions of pannexin 1 in the eye - Kurtenbach, Sarah; Kurtenbach, Stefan; Zoidl, Georg (Frontiers in Cellular Neuroscience, 2014)
Pannexin 1 (Panx1) is a high-conductance, voltage-gated channel protein found in vertebrates. It has been shown that Panx1 is widely expressed in many organs and tissues, including sensory systems. In the eye, Panx1 is expressed in major divisions including the retina, lens and cornea. Panx1 is found in different neuronal and non-neuronal cell types and localizes in strategic positions. The channel is mechanosensitive, and responds to changes in extracellular ATP, intracellular calcium, pH, or ROS/nitric oxide. Since Panx1 channels operate at the crossroad of major signaling pathways, physiological functions in important autocrine and paracrine feedback signaling mechanisms were hypothesized. This review summarizes known functions and outlines emerging roles of Panx1 in the eye demonstrating that this versatile channel is involved in multiple functions ranging from processing of visual information in the outer retina, to a crosstalk between immune and neural cells, pressure related pathological conditions like glaucoma, wound repair or neuronal cell death caused by ischemia.